Developing multiplayer networked game using python - Ahmad Irshad Abdul Hamid (2023)
Computer games have grown gradually in scale and complexity during the past few decades of computer game development throughout the world. Most of the modern computer games have reached the advanced standard of quality in 3D graphics and artificial intelligence.